Circular RNA hsa_circ_0007364 increases cervical cancer progression through activating methionine adenosyltransferase II alpha (MAT2A) expression by restraining microRNA-101-5p. Issue 1 (1st January 2020) - Chen, Hongfei; Gu, Bin; Zhao, Xiang; Zhao, Yupeng; Huo, Shuning; Liu, Xiang; Lu, Huihong
ABSTRACT: Emerging evidence suggested that circular RNAs (circRNAs) play critical roles in cervical cancer (CC) progression. However, the roles and molecular mechanisms of hsa_circ_0007364 in the tumorigenesis of CC remain unclear. In the present study, we used bioinformatics analysis and a series of experimental analysis to characterize a novel circRNA, hsa_circ_0007364 was up-regulated and associated with advanced clinical features in CC patients. Hsa_circ_0007364 inhibition notably suppressed the proliferation and invasion abilities of CC cells in vitro and reduced tumor growth in vivo. Moreover, hsa_circ_0007364 was uncovered to sponge miR-101-5p. Additionally, methionine adenosyltransferase II alpha (MAT2A) was verified as a target gene of miR-101-5p, and its downregulation reversed the inhibitory effects of hsa_circ_0007364 knockdown on CC progression. Therefore, we suggested that hsa_circ_0007364 might serve as an oncogenic circRNA in CC progression by regulating the miR-101-5p/MAT2A axis, which provides a potential therapeutic target to the treatment. Research highlights hsa_circ_0007364 was upregulated in CC hsa_circ_0007364 promoted CC cell progression hsa_circ_0007364/miR-101-5p/MAT2A axis in CC Graphical abstract: